Characterization of Industrial Black Mass from End-of-Life LiFePO4-Graphite Batteries - Nanna Bjerre-Christensen; Caroline Birksø Eriksen; Kristian Oluf Sylvester-Hvid; Dorthe Bomholdt Ravnsbæk (Batteries)
The use of Li-ion batteries is drastically increasing, especially due to the growing sales of electric vehicles. Simultaneously, there is a shift towards exchanging the traditional Co- and Ni-rich electrode materials with more sustainable alternatives such as LiFePO4. This transition challenges conventional recycling practices, which typically rely on shredding batteries into a substance known as black mass, which is subsequently processed via hydrometallurgical or pyrometallurgical methods to extract valuable elements. These routes may not be economically viable for future sustainable chemistries with lower contents of high-value metal. Hence, new methods for processing the black mass, allowing, e.g., for physical separation and direct recycling, are direly needed. Such developments require that the black mass is thoroughly understood. In this study, we thoroughly characterize a commercially produced Graphite/LFP black mass sample from real battery waste using a suite of analytical techniques. Our findings reveal detailed chemical, morphological, and structural insights and show that the components in the black mass have different micro-size profiles, which may enable simple size separation. Unfortunately, our analysis also reveals that the employed processing of battery waste into black mass leads to the formation of an unknown Fe-containing compound, which may hamper direct recycling routes.